Nilotinib: evaluation and analysis of its role in chronic myeloid leukemia. (February 2011) - Garland, Paula; Apperley, Jane
Nilotinib, formally known as AMN107, is a second-generation tyrosine kinase inhibitor, rationally designed from its revolutionary parent compound imatinib, to produce a 30––40-fold enhancement in the inhibition of the BCR––ABL1-derived oncoprotein associated with chronic myeloid leukemia. In clinical trials, nilotinib has proven to be a useful agent in the treatment of imatinib-refractory disease and was initially approved by both the US FDA and EMA in 2007 for use in adults as a second-line therapy. More recently, data from the first randomized controlled trials of the front-line use of nilotinib in newly diagnosed patients with chronic phase chronic myeloid leukemia have demonstrated superiority in the rates of major molecular responses at 12 months over the gold standard––imatinib 400 mg. As such, in June 2010, the FDA granted accelerated approval for its use in newly diagnosed Philadelphia chromosome-positive chronic myeloid leukemia. Nilotinib is well tolerated, with a favorable side-effect profile. With the emergence of supportive trial data, it is likely to have a leading role both in the front-line management of newly presenting patients and in the second-line treatment of patients resistant to or intolerant of imatinib and other second-line agents.